2016
DOI: 10.1021/acssuschemeng.6b00499
|View full text |Cite
|
Sign up to set email alerts
|

Water-Based Organic–Inorganic Hybrid Coating for a High-Performance Separator

Abstract: With the development of electric vehicles, the traditional polyolefin separators can not meet the increasing requirements of lithium ion batteries with high power density, high energy density, and high safety performance. Herein, a novel water-based binder is synthesized by grafting carboxyl groups onto cellulose diacetate. When the polyethylene (PE) separator is coated by this binder and SiO 2 nanoparticles, the thermal shrinkage of the modified separator is observed to be almost 0% after exposure at 200°C fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 47 publications
0
28
0
Order By: Relevance
“…Owing to the good electrolyte affinity of SiO 2 combined with a water‐based cellulose diacetate (CDA) coating on the PE separator, the prepared SiO 2 /CDA@PE possesses a higher electrolyte wettability and uptake as well as Li + transport ability, as evidenced by an improved t Li + (from 0.33 in PE to 0.36) (code 1–7). [ 66 ] The same group of researchers also attached the SiO 2 /CDA composite to both sides of the PE surface via a dip‐coating process. [ 67 ] They found that the pore structure of the coating layer is regulated by the weight ratio of the SiO 2 precursor tetraethoxysilane (TEOS) to CDA in the coating solution (Figure 2d).…”
Section: Composite Polymer Separator For Conventional Li‐based Secondmentioning
confidence: 99%
See 2 more Smart Citations
“…Owing to the good electrolyte affinity of SiO 2 combined with a water‐based cellulose diacetate (CDA) coating on the PE separator, the prepared SiO 2 /CDA@PE possesses a higher electrolyte wettability and uptake as well as Li + transport ability, as evidenced by an improved t Li + (from 0.33 in PE to 0.36) (code 1–7). [ 66 ] The same group of researchers also attached the SiO 2 /CDA composite to both sides of the PE surface via a dip‐coating process. [ 67 ] They found that the pore structure of the coating layer is regulated by the weight ratio of the SiO 2 precursor tetraethoxysilane (TEOS) to CDA in the coating solution (Figure 2d).…”
Section: Composite Polymer Separator For Conventional Li‐based Secondmentioning
confidence: 99%
“…For example, a separator coated with heat‐resistant SiO 2 nanoparticles with the help of polymeric binders exhibits reduced thermal shrinkage regardless of the type of SiO 2 when exposed to the same conditions (code 2–1–2–3). [ 62,63,66 ] Wang and co‐workers [ 66 ] investigated separator impedance with increasing temperature for a more detailed analysis of the thermal behavior of SiO 2 ‐coated separators ( Figure a). They found that a bare PE separator breaks down at 175 °C, while a SiO 2 ‐coated PE can maintain mechanical integrity until 200 °C, indicating that the SiO 2 coating is beneficial for separators that may be subjected to the self‐protecting stage for longer periods of time.…”
Section: Composite Polymer Separator For Conventional Li‐based Secondmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, surface grafting of functional groups and/or polymers could minimize the thickness increase and maintain the microporous structure (Yu et al., 2016). Although the modified polyolefin separators show improved wettability and thermostability, they are also hydrophilic (Chen et al., 2016, Dai et al., 2016, Ryou et al., 2011). Thus, moisture uptake is inevitable during the use and storage periods, which is unfavorable for the assembly and performance of Li batteries, especially for Li metal batteries.…”
Section: Introductionmentioning
confidence: 99%
“…The separator is a crucial component of LIBs. Its properties and structure play an indirect but key role in influencing the cell performance, including service life, energy density, power density, and safety [8,9]. Hence, several factors must be considered while choosing suitable separators for LIBs.…”
Section: Introductionmentioning
confidence: 99%